L. fermentum CECT 5716 prevents stress‐induced intestinal barrier dysfunction in newborn rats. Issue 8 (31st March 2017) - Vanhaecke, T.; Aubert, P.; Grohard, P.‐A.; Durand, T.; Hulin, P.; Paul‐Gilloteaux, P.; Fournier, A.; Docagne, F.; Ligneul, A.; Fressange‐Mazda, C.; Naveilhan, P.; Boudin, H.; et al.
Abstract: Background: Intestinal epithelial barrier (IEB) dysfunction plays a critical role in various intestinal disorders affecting infants and children, including the development of food allergies and colitis. Recent studies highlighted the role of probiotics in regulating IEB functions and behavior in adults, but their effects in the newborn remain largely unknown. We therefore characterized in rat pups, the impact of Lactobacillus fermentum CECT 5716 (L. fermentum) on stress‐induced IEB dysfunction, systemic immune response and exploratory behavior. Methods: Newborn rats received daily by gavage either L. fermentum or water. Intestinal permeability to fluorescein sulfonic acid (FSA) and horseradish peroxidase (HRP) was measured following maternal separation (MS) and water avoidance stress (WAS). Immunohistochemical, transcriptomic, and Western blot analysis of zonula occludens‐1 (ZO‐1) distribution and expression were performed. Anxiety‐like and exploratory behavior was assessed using the elevated plus maze test. Cytokine secretion of activated splenocytes was also evaluated. Key Results: L. fermentum prevented MS and WAS‐induced IEB dysfunction in vivo . L. fermentum reduced permeability to both FSA and HRP in the small intestine but not in the colon. L. fermentum increased expression of ZO‐1 and prevented WAS‐induced ZO‐1 disorganization in ileal epithelial cells. L. fermentum also significantly reduced stress‐induced increase in plasma corticosteronemia. In activated splenocytes, L. fermentum enhanced IFNγ secretion while it prevented IL‐4 secretion. Finally, L. fermentum increased exploratory behavior. Conclusions & Inferences: These results suggest that L. fermentum could provide a novel tool for the prevention and/or treatment of gastrointestinal disorders associated with altered IEB functions in the newborn. Abstract : CECT5716 (L. fermentum) strain prevented stress‐induced changes in permeability in vivo and reduced small intestinal but not colonic permeability. In addition, L. fermentum reduced stress‐induced changes in tight junction organization. L. fermentum enhanced exploratory behavior and increased IFNγ production in splenocytes. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterology-motility-august-2017/id1247431887 Youtube:https://youtu.be/7aY9zq36BZ4